Librarians' perceptions of educational values of comic books: A comparative study between Hong Kong, Taiwan, Japan, Australia and New Zealand. (December 2019) - Lo, Patrick; Allard, Bradley; Ho, Kevin K.W.; Chen, Joyce Chao-chen; Okada, Daisuke; Stark, Andrew; Henri, James; Lai, Chung-chin
Comic books are becoming increasingly popular in the field of education. In the past, comic books were excluded from school libraries and classrooms. However, with the resurgence in the popularity of comic books and students' increased demands for them, they are now considered as recreational reading with educational value. In response to this, school libraries have begun collecting comic books and including them as part of their regular collections. This research paper reflects on the current situation of comic books in primary and middle school library collections and examines school librarians' perceptions towards educational values of comics. The investigation was launched in Hong Kong, Taiwan, New Zealand, Australia and Japan – making comparisons amongst different levels (primary school and secondary school), and different types (public school and private school) of schools in five different countries. Questionnaire surveys were sent to selected school librarians and were the main method of data collection. A total number of 683 responses were collected for this study. Research results include librarians' attitudes towards comic books in school libraries, adolescent readers' use of school libraries, their reading and borrowing practices, as well as other problems encountered with the on-going maintenance of comic books as part of the school libraries' regular collections.